A chip-based potentiometric sensor for a Zika virus diagnostic using 3D surface molecular imprinting. Issue 14 (10th June 2019) - Ricotta, Vincent; Yu, Yingjie; Clayton, Nicholas; Chuang, Ya-Chen; Wang, Yantian; Mueller, Steffen; Levon, Kalle; Simon, Marcia; Rafailovich, Miriam
Abstract : The high sensitivity and high selectivity demonstrated here proved that this lab-on-a-chip diagnostic has the potential to become a point-of-care (POC) detection system for rapid and accurate screening of flaviviruses. Abstract : The latest Zika virus (ZIKV) pandemic caused great international concern from explosively proliferating throughout the Americas. Currently, there is no vaccine to prevent Zika virus infection and available tests rely on antibodies or RNA. Unfortunately, antibody-based detection systems can result in false positive results and RNA-based detection systems are costly, time-consuming, and impractical for testing in remote regions. In this study, a potential point-of-care (POC) diagnostic system was developed using a chip-based potentiometric sensor to detect Zika virus using a 3D molecular imprinting technique. This chip-based potentiometric sensor system was able to detect 10 −1 PFU mL −1 ZIKV in a buffered solution under 20 minutes without any sample manipulation. This sensor was tested against Dengue virus at clinical viral loads and showed no sign of cross-reactivity. When tested against human saliva samples containing clinical viral loads, this sensor was able to detect 10 PFU mL −1 ZIKV among the pool of bio-macromolecules. The high sensitivity and high selectivity demonstrated here proved that this lab-on-a-chip diagnostic has the potential to become a POC detection system for rapid and accurate screening of flaviviruses.